Resistencias pedagógicas: experiencias de educación de personas jóvenes y adultas en Bogotá (2021)
This work takes in individual and colective narratives generated from social organizations and the National Pedagogic Institute (NPI) before the fights for the garantee of education rights all throughout life, taking as a guide their visions and ethic-politic experiences. The book formulates a series of categories to reflect and historicize the experiences in the education of young and adult people, narrated from the incorporeal relationships that propiciate the rupture of pedagogical, didactical and educative parameters. In this way, the authors documentate encounters located in diferent space-times trough the sistematization of experiences and the popular education in regard of problematize the hegemonic places of research and epistemology with the normalizer pedagogy.